POLICIES OF EXCLUSION: IMPLICATIONS FOR THE HEALTH OF IMMIGRANTS AND THEIR CHILDREN - Perreira, Krista M. (Annu Rev Public Health, 2019)
Immigrants to the U.S. face the challenge of adapting to life in a new country with a different culture, norms, and social institutions. These social institutions include an array of federal, state, and municipal laws and administrative practices that can either facilitate or hinder immigrant integration. Guided by a structural framework for understanding social determinants of health, this review examines the literature on immigration-related policies that influence the health of immigrants. We begin with an overview of the pathways through which policies can influence health. We then discuss empirical research strategies for identifying the effects of policies on health. Next, we review evidence from federal welfare and health reforms, local immigration enforcement activities, and state and local immigrant integration policies. Our conclusion highlights the gaps in existing research and the steps that can be taken to better promote the health of immigrants and, consequently, their economic and social integration.